Traffic Density Prediction Model At Loading Terminal Using Discrete Simulation Method Quantitative Approach - Indriyani, Kristin Anita; Sulistiyowati, Ely; Nurhidayati, Indah (Nama Jurnal Akmi, 2023)
Traffic density at the port loading terminal is a critical factor affecting the port's operational efficiency and overall performance. To overcome the challenges of the complexity of the traffic system at the port terminal, a discrete simulation approach is adopted in this study. A quantitative approach is used to collect data and accurately model traffic processes. This study aims to develop a predictive model of traffic density at Tanjung Emas port loading terminals using a discrete simulation methods quantitative approach. The results showed that the resulting traffic density prediction model has high accuracy and can be used as a predictive tool to assist decision-making in optimizing port loading terminal operations